Fixing the Universe. Fan-Based Practices Between Narrative Ecosystems and Participatory Media - Villa, Pierandrea (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
Fan communities are groups of possessive spectators who, as Laura Mulvey (2006) states, can undermine the aesthetic integrity and narrative cohesion of media artefacts within the franchise of their choice, regardless of copyright regulations. In this context, user-generated content can be interpreted as a renegotiation of a power structure that can prompt a rediscussion of critical issues such as the representation of minority groups (Brembilla 2023). Furthermore, fans’ intellectual capital, together with their emotional connection to the franchise (Jenkins 2006b), can lead the former to reject a particular segment of the latter, presenting a scenario in which fandom and anti-fandom coexist (Click 2019). Therefore, fans can interact with a franchise by modifying and remixing its content to “repair” elements that they perceive as inconsistent with the franchise’s quality standards and values. With these considerations in mind, this essay aims to analyse two specific fan-based practices within the context of the Marvel Cinematic Universe: fanedits – fan-made alternative montages of a particular film – and fandom universes – fan-made redefinitions of a narrative ecosystem as a whole. Following this analysis, it is possible to understand how current intellectual property management strategies can nourish new forms of copyright infringement.